Factors Affecting the Intention to Use Digital Banking: An Empirical Study from an Emerging Economy - Hossain, Mohammad Azhar (Finance & Economics Review, 2024)
Purpose: Banks are adopting digital banking to attract clients by providing more useful services, and creating safe, dependable, and easy-to-use online tools. The purpose of this research is to examine the factors influencing the overall adoption of digital banking by retail banking customers. Methods: An expanded technology acceptance model (TAM) serves as the basis for the theoretical framework of the study. A structured survey of 200 consumers is used to gather primary data, and multiple regression analysis is used to examine the correlations between six independent components. Results: The research indicates that web capabilities, perceived utility, and awareness all have a positive and significant impact on the adoption of digital banking. Implications: This study offers guidelines for creating service models and boosting the use of digital banking. The findings can help policymakers and financial organizations devise strategies for constructing the infrastructure and methods for offering digital banking services. Originality: It is a pioneering effort to explore the combined effects of Perceived usefulness, usability, Privacy, safety, trust Cost of transactions Awareness and Web features on Bangladeshi users’ intention to use digital banking. Limitations: This study is based on quantitative data analysis with limited sample size and period. In future, qualitative research may be conducted for deeper understanding of the issue.